Liberalism, childhood and justice : ethical issues in upbringing - Fowler, Tim, 1983- (Bristol University Press, 2020)
Fowler combines political philosophy with sociological perspectives for an innovative critical exploration of ethical issues in children's upbringing, calling for a radical new understanding of what constitutes wellbeing, the duties of parents and the collective obligations of state and society in guaranteeing children flourishing lives.